2020
DOI: 10.1167/tvst.9.12.29
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anti-Amoebic Agents and Ce6-PDT onAcanthamoeba castellaniiTrophozoites and Cysts, In Vitro

Abstract: The purpose of this study was to analyze the concentration-dependent effects of biguanides (polyhexamethylene biguanide [PHMB], chlorhexidine [CH]); diamidines (hexamidine-diisethionate [HD], propamidine-isethionate [PD], dibromopropamidinediisethionate [DD]); natamycin (NM); miltefosine (MF); povidone iodine (PVPI), and chlorin e6 PDT on Acanthamoeba trophozoites and cysts, in vitro. Methods: Strain 1BU was cultured in peptone-yeast extract-glucose medium. Trophozoites or cysts were cultured in PYG medium con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…While generally, the cytotoxicity measured with the LDH assay was similar to that reported for A. castellanii on HCECs in a previous study ( Sohn et al, 2019 ), we found that the LDH assay underestimated the proportion of dead cells and overestimated the proportion of living cells and thus was not reliable to determine the cytotoxic effect of Acanthamoeba on HCECs. However, the LDH assay has also been used to evaluate the activity of potentially anti-amoebic agents, because this enzyme is released into the culture medium when the cell membrane integrity is affected ( Sissons et al, 2005 ; Lorenzo-Morales et al, 2010 ; Anwar et al, 2018 ; Shi et al, 2020 ; Akbar et al, 2022 ). The results obtained in the current study corroborate the suitability of the LDH assay for evaluating Acanthamoeba viability, but not when Acanthamoeba is co-cultured with other cells.…”
Section: Discussionmentioning
confidence: 99%
“…While generally, the cytotoxicity measured with the LDH assay was similar to that reported for A. castellanii on HCECs in a previous study ( Sohn et al, 2019 ), we found that the LDH assay underestimated the proportion of dead cells and overestimated the proportion of living cells and thus was not reliable to determine the cytotoxic effect of Acanthamoeba on HCECs. However, the LDH assay has also been used to evaluate the activity of potentially anti-amoebic agents, because this enzyme is released into the culture medium when the cell membrane integrity is affected ( Sissons et al, 2005 ; Lorenzo-Morales et al, 2010 ; Anwar et al, 2018 ; Shi et al, 2020 ; Akbar et al, 2022 ). The results obtained in the current study corroborate the suitability of the LDH assay for evaluating Acanthamoeba viability, but not when Acanthamoeba is co-cultured with other cells.…”
Section: Discussionmentioning
confidence: 99%
“…isolates of sequence types T4 and T6. In the process, the focus was on cysts, the dormant stage of this amoeba, which are usually less susceptible to drug treatment than the actively dividing trophozoites [8,14]. We treated the cyst suspension with each drug for 2 h, then diluted the cysts and drug suspension by 100-fold, and placed an aliquot of the diluted cyst/drug mixture onto the center of a non-nutrient agar E. coli plate, thereby transferring lower concentrations of the drug onto the test plate.…”
Section: Discussionmentioning
confidence: 99%
“…Peptone-yeast-glucose medium (PYG), Neff's constant-pH encystment medium, and Page's amoeba saline (PAS) were prepared as described in [8]. For the non-nutrient agar, 15 g of agar (Sigma-Aldrich) was mixed with 100 mL PAS and 900 mL distilled water and autoclaved at 121 • C for 15 min.…”
Section: Medium and Non-nutrient Agar Preparationmentioning
confidence: 99%
See 2 more Smart Citations